The combination of atrial fibrillation and small vessel disease score worsen spontaneous intracerebral hemorrhage outcomes - Hamada, Yuki; Sato, Takeo; Matsuoka, Hideki; Tsuchimochi, Yuka; Kukihara, Kaishi; Kawabata, Yutaro; Iwamoto, Kana; Takaguchi, Go; Higuchi, Yujiro; Takashima, Hiroshi (Frontiers in Neurology, 2025)
BackgroundThis study aimed to examine whether the presence of atrial fibrillation (AF), severity as judged by total small vessel disease (SVD) score, or a combination of these is associated with prognosis and hematoma volume of spontaneous intracerebral hemorrhage (sICH).MethodsThis retrospective analysis investigated 608 patients who were admitted within 7 days of ICH onset between July 2012 and November 2023. The primary outcome was prognosis at 3 months after onset according to the modified Rankin Scale (mRS) score. Associations of AF, SVD and a combination of these with outcomes and hematoma volume were examined using univariate analyses, logistic regression analysis, and multiple regression analysis.ResultsA total of 608 consecutive patients with sICH were screened, and 330 patients were finally included in the analysis after applying the inclusion and exclusion criteria. Among the 330 patients analyzed, 145 (43.9%) experienced poor outcomes (mRS score 4–6). The presence of AF was independently associated with poor outcome (adjusted OR 4.93, 95% CI 1.72–16.1; p = 0.002), whereas total SVD score alone was not. Multiple regression analysis with estimated hematoma volume also showed a significant association with AF (standard partial regression coefficient 0.16; p = 0.033), but not with total SVD score. However, a linear trend was observed between the combination of AF and total SVD score severity and poor outcome (total SVD score 0–1 without AF: aOR 1.00, total SVD score 2–4 without AF: 1.44, total SVD score 0–1 with AF: 4.26, total SVD score 2–4 with AF: 7.57; p for trend = 0.002). Multiple regression analysis using estimated hematoma volume also showed a synergistic effect of AF and total SVD score severity (standardized regression coefficient 0.14; p = 0.032).ConclusionThe presence of AF was associated with poor 3-month outcomes and increased estimated hematoma volume in sICH patients, whereas total SVD score alone was not. The effects of AF and SVD together appear to contribute synergistically to worsened prognosis and increased hematoma volume in sICH patients.